A Doctor in the House : My Life With Ben Carson - Carson, Candy (New York, New York : Sentinel, 2016)
The wife of pioneering surgeon and presidential candidate Ben Carson offers an intimate portrait of her husband as a family man, Christian, and patriot that shares insights into his beliefs about how all Americans are capable of remarkable achievements.
Keywords: Carson, Ben; Carson, Candy; Presidential candidates -- United States; Biography; African American presidential candidates -- Biography; Neurosurgeons -- United States; Biography; Physicians spouses -- United States; Biography